Prevalence of Child Functional Difficulties and Its Associated Factors in Bangladesh: An Application of Count Regression Model. (27th December 2022) - Habib, Md. Jakaria; Hossain, Md. Ismail; Haq, Iqramul; Methun, Md. Injamul Haq; Sakib, Md. Saifullah
Abstract : Children that are mentally and physically healthy have a higher quality of life and are better able to function in their daily lives. Therefore, this study is aimed at investigating associated factors causing functional difficulties in male and female children ages 5-17 years. This study used data from a nationally representative cross-sectional household survey named the Multiple Indicator Cluster Survey (MICS) Bangladesh 2019. A total of 58, 746 children aged 5-17 were selected for the study, where 30, 300 children were male, and 28, 446 were female. To deal with overdispersed count data, the study used a negative binomial regression model to find the associated factors. The results show that 39.3% of the male children and 40.9% of the female children were from the age group of 10-14. Educated children had a lower risk of dysfunction. Among male children, women with a total number of children ever born of 4 or more were 1.21 times (incidence rate ratios IRR = 1.21 ) more likely to have a dysfunctional child. Children of dysfunctional mothers are more likely to be dysfunctional themselves. The incidence rate ratio for children functional difficulty among Muslim girls was 36 percent higher than non-Muslim girls in Bangladesh. When compared to the Barisal Division, female children in the Mymensingh Division had a 16% higher risk of functional problems. Based on the findings, the Bangladesh government and other development partners should initiate policies and programs to minimize the impact of functional dysfunction in children.